The Effect of Moral Reasoning on Intention to Fraud in the Procurement of Goods and Services under Obedience Pressure: An Experimental Study - Edy Sujana; Nyoman Ayu Wulan Trisna Dewi (Universitas Pendidikan Ganesha, 2021)
This study examines the influence of obedience pressure and individual moral reasoning on the attention to commit fraud in the context of the procurement of goods and services. This study uses a 2x2 factorial experimental design. The participants in this study were undergraduate accounting students who have passed courses in Professional Ethics, Public Sector Accounting, and Forensic Accounting who acted as implementers of the procurement of goods and services. Hypothesis testing in this study used ANOVA. The results of this study found the effect of obedience pressure and individual moral reasoning in committing fraud in the procurement of goods and services. Under conditions of obedience pressure, individuals with low moral reasoning will tend to commit fraud compared to individuals with high moral reasoning. Thus, individuals who have high moral reasoning tend to behave ethically, even though they are faced with pressure from superiors.